Análisis de la planta turística, oferta alojamiento en el Cantón Salcedo, Provincia de Cotopaxi - Pérez Guanoluisa, Lesly Antonela (2019)
The project was carried out in the Salcedo canton, belonging to the province of Cotopaxi, which intends to carry out an analysis of the tourist facilities available on the site, because the current status of the study area is unknown, for which a diagnosis was made situational for the purpose of collecting, analyzing and synthesizing information to obtain general data. An information registry was carried out through the application of a technical file, which was responsible for collecting the main information, evaluating the type of infrastructure and equipment, as well as the services that can be provided to the tourist. As a result, an inventory was obtained the existing establishments in the Salcedo canton.The results showed the existence of 8 establishments, among which we have a hotel that has a category of two stars, three hostels that are in the category of one star and four hostels that have a category of four stars. It was concluded with the preparation of a catalog, which includes general information of each establishment such as: name, address, telephone, mail, website, services, prices and photographs. The catalog is designed for the purpose of disseminating information ordered.Seeing the need to expand the tourist offer of the Salcedo canton and implement new ways to reach the tourist and capture their attention, we proceeded to conduct a field investigation, which showed the lack of interest on the part of several of the owners and those responsible for the establishments that provide the hosting service. This, giving us a clear picture of the reality presented by the local service, boosted creativity and commitment to the creation of this catalog, in turn, seeks to take advantage of each of the tourist attractions of the canton to grow as a tourist power and be recognized nationally and internationally. It is expected, in addition, that the present research project serves as a base and point of reference, so that future researchers can continue with investigations that deepen other factors of the tourism sector and thus be able to reach excellence.